The Politics of Listening : Possibilities and Challenges for Democratic Life - Bassel, Leah (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2017)
This book explores listening as a social and political practice, in contrast to the more common focus on voice and speaking. The author draws on cases from Canada, France and the United Kingdom, exploring: minority women and debates over culture and religion; riots and young men in France and England; citizen journalism and the creative use of different media; and solidarity between migrant justice and indigenous activists. Analysis across these diverse settings considers whether and how a politics of listening, which demands that the roles of speakers and listeners change, can be undertaken in adversarial and tense political moments. The Politics of Listening argues that such a practice has the potential to create new ways of being and acting together, as political equals who are heard on their own terms. The book will appeal to students and scholars across a range of disciplines, including sociology and political theory.- Resumé vydavatel
Keywords: sociologie politiky; politická komunikace; sociální nerovnost; sociální struktura; political sociology; communication in politics; social inequality; social structure; elektronické knihy; monografie; electronic books; monographs